Screening and fermentation performance of superior yeasts for koumiss fermentation in Yili region - TANG Xian, WU Yun, TIAN Tian, LUO Xiaohong, CHEN Weilin, MA Wenrui, FU Zhiang, TANG Kai, WANG Meiqi (Zhongguo niangzao, 2024)
In order to explore safe and efficient yeast strains for koumiss fermentation, 10 traditional koumiss samples were collected from Yili area, the strains were separated and purified by dilution coating method, primarily screened by gas production and ethanol production capacity, rescreened by tolerance analysis and safety evaluation, the excellent yeast strains were screened, and the screened strains were identified by molecular biology techniques. The screened yeasts were applied to koumiss fermentation, the fermentation performance of the selected strain was investigated by measuring the physicochemical index and sensory quality of koumiss. The results showed that 3 superior yeast strains were isolated and screened, numbered as TX1-2, TX1-6, and TX3-1, respectively, all of which could withstand pH 3.0, high temperature 45 ℃, and ethanol volume fraction 6%, without hemolysis. They didn't have resistance to antifungal drugs itraconazole, fluconazole, voriconazole, and amphotericin B. After identification, the strain TX1-2 was Starmerella davenportii, the strain TX1-6 was Saccharomyces cerevisiae and the strain TX3-1 was Kluyveromyces marxianus. There were no significant differences in the protein and fat contents between koumiss fermented by 3 superior yeast strains and those of natural fermentation and koumiss with commercial Saccharomyces cerevicae CVE-7 fermentation (P>0.05), there were some differences in pH and lactose content, and the alcohol content was significantly decreased (P<0.05), but the physicochemical indexes were in line with the relevant standards. The sensory scores of koumiss fermented by strains TX1-6 and TX3-1 were higher, which were 89.40 and 91.20, respectively, indicating that the strains TX1-6 and TX3-1 had more potential to ferment koumiss.